Multiple intramolecular triggers converge to preferential G protein coupling in the CB2R - Adrian Morales-Pastor; Tamara Miljuš; Miguel Dieguez-Eceolaza; Tomasz Maciej Stępniewski; Vicente Ledesma-Martin; Franziska M. Heydenreich; Tilman Flock; Bianca Plouffe; Christian Le Gouill; Jean Duchaine; David A. Sykes; Colin Nicholson; et al. (Nature Communications)
Abstract G protein-coupled receptors (GPCRs) are important therapeutic drug targets for a wide range of diseases. Upon activation, GPCRs can initiate several signaling pathways, each with unique therapeutic implications. Therefore, understanding how drugs selectively engage specific signaling pathways becomes paramount. However, achieving this selectivity remains highly challenging. To unravel the underlying multifaceted mechanisms, we integrate systematic mutagenesis of the CB2R, comprehensive profiling of Gαi2 and β-arrestin1 engagements and computer simulations to track the effects of mutations on receptor dynamics. Our research reveals multiple triggers within a complex allosteric communication network (ACN) that converge to preferential CB2R coupling by modulating evolutionarily conserved motifs. Utilizing network path analysis, we find that potent triggers are typically highly connected nodes and are located near regions of high information transmission within the ACN. Our insights highlight the complexity of GPCR signaling and provide a framework for the rational design of drug candidates tailored to evoke specific functional responses, ultimately enhancing the precision and efficacy of therapeutic interventions.